Association between tactile over‐responsivity and vegetable consumption early in the introduction of solid foods and its variation with age. Issue 4 (21st January 2016) - Coulthard, Helen; Harris, Gillian; Fogel, Anna
Abstract: The main aim of the current study was to test the hypothesis that early reactions to a vegetable in infants may be associated with sensory processing, in particular, tactile over‐responsivity. A secondary aim was to see whether the relationship between sensory over‐responsivity and vegetable consumption would be moderated by the age of the infant. A sample of 61 infants was recruited from children's centres and playgroups in South Birmingham, UK. Infant's acceptance of carrot was measured in grams during the first week of complementary feeding in one testing situation. Mothers filled in self‐report measures of infant sensory processing, as well as their own fruit and vegetable consumption. Infant carrot consumption in the first week of solid food consumption was negatively associated with total sensory over‐responsivity across different sensory domains ( P < 0.01). Across the sensory domains only tactile over‐responsivity predicted carrot consumption, accounting for 10.7% of the variance in consumption scores. Across the sample as a whole, the relationship between carrot consumption and tactile over‐responsivity varied according to the age of introduction to solid foods. In particular, those who were weaned later and had high tactile over‐responsivity ate less carrot ( P < 0.001). Infants who were weaned early ate a similar amount of carrot, regardless of their tactile responsivity ( P > 0.05). This study constitutes some of the first evidence to suggest that sensory processing styles be associated with early vegetable acceptance; however, more research is needed to evaluate the best strategies to use when feeding infants who are sensitive to tactile information.